Bay window at end of Corporation Hall - Ghosh, Ayan (Jio Institute, 2023)
Frederick W. Stevens had originally designed a full-height bay window decorated with stained glass at one end of the Corporation Hall. Light entering through this window naturally illuminated the hall. In front of this bay window was a raised platform used by speakers. This arrangement was later changed, with the raised platform now moved to the side.